The Effectiveness of Positive Self-Talk Training on Self-Esteem and Achievement Motivation in Depressed Students Preparing for the University Entrance Exam - Saket Ghalb Langeroodi, Shadi; Fakhrieh Kashani, Hanieh; Ilkhaniha, Rozhin; Amiri, Fatemeh; Madankan, Nastaran (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The present study aimed to examine the effectiveness of positive self-talk training in enhancing self-esteem and achievement motivation among depressed students preparing for university entrance exams.Methods and Materials: This study employed a quasi-experimental design using a pretest-posttest control group format. The statistical population consisted of all depressed students preparing for university entrance exams in Tehran during the 2024–2025 academic year. From this population, 30 students were selected through convenience sampling based on specific inclusion and exclusion criteria. Participants were randomly assigned to either the experimental group (n = 15) or the control group (n = 15). Data were collected using the Coopersmith Self-Esteem Inventory (CSEI) and the Hermans Achievement Motivation Test (HAMT). The experimental group underwent ten 45-minute sessions of positive self-talk training. Data analysis was conducted using analysis of covariance (ANCOVA) via SPSS software (version 23).Findings: The findings revealed that the mean scores for self-esteem and achievement motivation significantly increased in the experimental group compared to the control group following the intervention (F = 22.23, p < .05). Effect size analysis indicated that 76% of the variance in self-esteem and 72% of the variance in achievement motivation between the groups could be attributed to the positive self-talk training.Conclusion: Given the results, positive self-talk training appears to be an effective psychological strategy for improving self-esteem and achievement motivation among depressed students preparing for university entrance exams.